Avatar Embodiment. A Standardized Questionnaire - Peck, Tabitha C.; Gonzalez-Franco, Mar (Frontiers in virtual reality, 2021)
The aim of this paper is to further the understanding of embodiment by 1) analytically determining the components defining embodiment, 2) increasing comparability and standardization of the measurement of embodiment across experiments by providing a universal embodiment questionnaire that is validated and reliable, and 3) motivating researchers to use a standardized questionnaire. In this paper we validate numerically and refine our previously proposed Embodiment Questionnaire. We collected data from nine experiments, with over 400 questionnaires, that used all or part of the original embodiment 25-item questionnaire. Analysis was performed to eliminate non-universal questions, redundant questions, and questions that were not strongly correlated with other questions. We further numerically categorized and weighted sub-scales and determined that embodiment is comprised of interrelated categories of Appearance, Response, Ownership, and Multi-Sensory. The final questionnaire consists of 16 questions and four interrelated sub-scales with high reliability within each sub-scale, Chronbach’s α ranged from 0.72 to 0.82. Results of the original and refined questionnaire are compared over all nine experiments and in detail for three of the experiments. The updated questionnaire produced a wider range of embodiment scores compared to the original questionnaire, was able to detect the presence of a self-avatar, and was able to discern that participants over 30 years of age have significantly lower embodiment scores compared to participants under 30 years of age. Removed questions and further research of interest to the community are discussed.